2019
DOI: 10.1002/dta.2572
|View full text |Cite
|
Sign up to set email alerts
|

Decarbonylation: A metabolic pathway of cannabidiol in humans

Abstract: Cannabidiol (CBD) is a non‐psychoactive cannabinoid, which is of growing medical interest. Previous studies on the metabolism of CBD showed mainly the formation of hydroxylated or oxidized derivatives, the formation of carboxylic acids or modifications of the aliphatic side chain. Using incubation of CBD with hepatic microsomes of mice, the formation of carbon monoxide was reported. We investigated the phase I metabolism of CBD and cannabidivarin (CBDV) using in vitro experiments with human liver microsomes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 31 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…The cannabinoids and their metabolites can be detected and measured in a variety of biological fluids, like blood plasma [147], saliva, and urine [148] to evaluate their intake and study their metabolism [149]. Therefore, a suite of different types of epileptic and neuroinflammatory biomarkers (especially the downstream mediators, such as IL-1β and COX-2 products) in conjunction with biomarkers of cannabinoid treatment (e.g., cannabinoids and their metabolites) could help to paint a more complete picture of the cannabinoids’ metabolic pathways, their toxicity, and their modes of action on the neuroinflammatory pathways.…”
Section: Biomarkers For Determining Neuroinflammation and Monitorimentioning
confidence: 99%
“…The cannabinoids and their metabolites can be detected and measured in a variety of biological fluids, like blood plasma [147], saliva, and urine [148] to evaluate their intake and study their metabolism [149]. Therefore, a suite of different types of epileptic and neuroinflammatory biomarkers (especially the downstream mediators, such as IL-1β and COX-2 products) in conjunction with biomarkers of cannabinoid treatment (e.g., cannabinoids and their metabolites) could help to paint a more complete picture of the cannabinoids’ metabolic pathways, their toxicity, and their modes of action on the neuroinflammatory pathways.…”
Section: Biomarkers For Determining Neuroinflammation and Monitorimentioning
confidence: 99%
“…CBD is known to have antitumor activity against Noxa activation, inhibition of mTOR/cyclin D1, and G-protein-coupled receptors/mitogen-activated protein kinase pathway in various cancers such as pancreatic 3,4 , glioblastoma 1 , colorectal 5 , and breast cancer 6 . It also has beneficial effects on brain function, metabolism, and pain reduction 7–9 . However, there have been few reports on the anticancer mechanism by CBD in gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…However, multiomics analysis has shown that CBD penetrates cell membranes, altering the chemical activity of cholesterol and increasing lipid order [ 59 ]. Cannabidiol is biotransformed in the liver, where decarbonylated CBD (DCBD) and 7-hydroxycannabidiol (7-OH-CBD) [ 60 , 61 ], observed in our study, are produced by cytochrome P450 (CYP) isoenzymes. 7-OH-CBD is known to be one of the metabolites of CBD generated by CYP2C19 of liver microsomes [ 61 ] and this study showed its level increases in the liver membrane fraction after UVA/UVB irradiation.…”
Section: Discussionmentioning
confidence: 99%